Избранное: [перевод с английского] / В. Шекспир - Шекспир Вильям (Просвещение, 1985)
Экземпляры: ф. 4 (20100128) / Инвентарный номер: 95801 / Цена: 30.00 / Авт.знак: Ш 41 / ГРНТИ: 17.82 / ББК: 84(4Вел)